Aplikasi Layanan Service Kendaraan Bermotor (Carimontir) Using Design Thinking Method - Krisna Sapari; Edi Hamdi (Universitas Batanghari, 2023)
Many ownership of vehicles is an opportunity for repair service owners in Indonesia, to plan operations on Carimontir's business plan, operational plans are carried out based on a strategic plan by setting operational objectives in line with the company's strategic plan in accordance with setting objectives. After determining operational objectives, Carimontir determines targets that in accordance with QSPM, namely the number of business partners and being anywhere & anytime. Then according to the business level strategy, namely the differentiation strategy by having artificial intelligence technology in the form of Chat Bots. The idea for the display of the application must be easy for everyone to understand by applying a minimalist design concept accompanied by symbols that imply the function of the user of the feature. In designing the Carimontir system process technology using the latest version of the system so that application work will run smoothly without lag, the latest security system is an important part of system security and company data.